2021
DOI: 10.1021/acsearthspacechem.0c00333
|View full text |Cite
|
Sign up to set email alerts
|

New Particle Formation and Growth from Dimethyl Sulfide Oxidation by Hydroxyl Radicals

Abstract: Dimethyl sulfide (DMS) is produced by plankton in oceans and constitutes the largest natural emission of sulfur to the atmosphere. In this work, we examine new particle formation from the primary pathway of oxidation of gas-phase DMS by OH radicals. We particularly focus on particle growth and mass yield as studied experimentally under dry conditions using the atmospheric simulation chamber AURA. Experimentally, we show that aerosol mass yields from oxidation of 50–200 ppb of DMS are low (2–7%) and that partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 100 publications
3
29
0
Order By: Relevance
“…Oxidation of DMS leads to the concurrent formation of MSA and SA. Based on quantum chemical calculations, Rosati et al 77 recently demonstrated that cluster formation involving (SA) x (MSA) y (A) 1−4 (with x + y ≤ 4) consisted of different mixtures of both SA and MSA molecules. Hence, exchanging one MSA molecule with SA might alleviate the identified deficiencies in the MSA-base system, as this leads to an additional S−OH group, thus increasing the hydrogen-bonding capacity of the clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of DMS leads to the concurrent formation of MSA and SA. Based on quantum chemical calculations, Rosati et al 77 recently demonstrated that cluster formation involving (SA) x (MSA) y (A) 1−4 (with x + y ≤ 4) consisted of different mixtures of both SA and MSA molecules. Hence, exchanging one MSA molecule with SA might alleviate the identified deficiencies in the MSA-base system, as this leads to an additional S−OH group, thus increasing the hydrogen-bonding capacity of the clusters.…”
Section: Discussionmentioning
confidence: 99%
“…By photolysing H 2 O 2 , OH radicals were produced. The OH radical concentrations in the experiments are estimated to be in the range of typical tropospheric concentrations (4.64-5.71E+06 molecules cm −3 ; Seinfeld and Pandis, 2016) based on supplementary experiments investigating the decay of 1-butanol in the bag (Rosati et al, 2021a, b;Wollesen de Jonge et al, 2021). Either 200 or 400 ppb of DMS (Sigma Aldrich, anhydrous ≥99.0 %, 274380) were injected into the chamber by evaporating a known amount and guiding it into the chamber using 10 L min −1 of N 2 gas heated to 333 K. The sequential order of the procedure was: 1) setting the desired chamber temperature, 2) filling the chamber with purified air (Active Carbon, HEPA filter and zero-air generator (Aadco Model 737-14)), 3) injecting humidified air to reach the desired RH, 4) injecting H 2 O 2 , 5) switching the UV lights on, 6) injecting DMS.…”
Section: Methodsmentioning
confidence: 99%
“…This work focuses on the water uptake of the studied aerosol particles, thus Exp. 1, 5, 6, 7 and 9 are presented in terms of the hygroscopicity and CCN activity, which were not addressed in any of the previous studies (Rosati et al, 2021a;Wollesen de Jonge et al, 2021). Analytik, Innsbruck, Austria; e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent DMS + OH oxidation experiments performed in the AURA chamber at Aarhus University show that MSA dominates the secondary aerosol mass formation . Aerosol dynamics model simulations which intended to replicate the observations during these AURA experiments, using the DMS gas-phase chemistry scheme from the Master Chemical Mechanism, MCMv3.3.1 (Jenkin et al, 1997(Jenkin et al, , 2015Saunders et al, 2003), substantially underestimate the particle mass and number concentrations and the MSA : SO 2− 4 ratio (Rosati et al, 2021;. Based on these findings, Wollesen de Jonge et al ( 2021) developed a new DMS multi-phase chemistry scheme based on MCM v3.3.1, CAPRAM DMS module 1.0 (DM1.0) (Hoffmann et al, 2016), a subset of the multiphase halogen chemistry mechanism CAPRAM Halogen Module 2.0 (HM2.0) (Bräuer et al, 2013), and new reactions leading to the formation of hydroperoxymethyl thioformate (HPMTF).…”
Section: Introductionmentioning
confidence: 98%